Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1136/vr.131.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic study of early embryonic loss induced by Actinomyces pyogenes in cattle

Abstract: Four cows were inoculated into the uterus with Actinomyces pyogenes between 30 and 41 days of gestation. Gross morphological changes were monitored by rectal palpation and with a realtime B-mode two-dimensional scanner with a 7.5 MHz transrectal linear transducer, shortly before infection and afterwards at three to 12 hours intervals. Two control groups of cows 27 to 50 days pregnant were used: two cows were inoculated with 6 ml of sterile saline into the uterine lumen and four cows were treated with cloproste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…One of the advantages of UEs is that PL can be recognized by the absence of a heartbeat, the detachment of the fetal membranes, the appearance of particles in the fetal fluids, or the lack of the embryo proper [25,128]. UEs have revealed that LEM may occur in up to 23% of pregnancies [28,129].…”
Section: Ultrasonographymentioning
confidence: 99%
“…One of the advantages of UEs is that PL can be recognized by the absence of a heartbeat, the detachment of the fetal membranes, the appearance of particles in the fetal fluids, or the lack of the embryo proper [25,128]. UEs have revealed that LEM may occur in up to 23% of pregnancies [28,129].…”
Section: Ultrasonographymentioning
confidence: 99%
“…THERE is evidence that Leptospira interrogans serovar hardjo localises in the genital tract of cattle (Ellis and others 1986). Uterine infections, such as bovine viral diarrhoea and Actinomyces pyogenes, alter the length of the oestrous cycle and cause embryonic death (Fredriksson and others 1988, Semambo and others 1992), but it is unknown whether hardjo is similarly pathogenic.…”
Section: Figurementioning
confidence: 99%
“…None of the embryos died during the study period, that is, a heartbeat was detected in all cases from day 30 onwards. However, embryonic deaths have been observed following intrauterine inoculation of other bacterial or viral infections during early pregnancy or around insemination (Carlsson and others 1989, Semambo and others 1992, McGowan and others 1993). No specific explanation can be offered for low progesterone concentrations during early to mid pregnancy in infected heifers compared to controls.…”
Section: Figurementioning
confidence: 99%
“…One of the advantages of UEs is that PL can be recognised by the absence of a heartbeat, the detachment of the foetal membranes, the appearance of particles in the foetal fluids or the lack of the embryo proper [49,50]. UEs have revealed that LEM may occur in up to 23% of pregnancies [12,51].…”
Section: Diagnosis Of Pregnancy Lossesmentioning
confidence: 99%